NNU Bike Campus Hub - Dima Eid; Sema Hodali (My University, 2024)
BikeCampusHub is a smart bike rental station system designed for students at university campuses. With the long distance between campuses, this project aims to provide an efficient and convenient mode of transportation for students which was inspired by European bike rental systems. The system contains a smart bike, a connected vest wirelessly, and rental stations that communicate continuously. Students have two ways to access bikes either by using their student ID or by receiving a verification code on their mobile phones. The system tracks essential student information, including phone numbers, student IDs, names, and rental status, ensuring that a student cannot rent another bike until the previous one is returned. Additionally, students can view all stations on their phones to check their availability, whether they have bikes, and whether they are active or deactivated by the admin. The system also provides real-time updates on the remaining time to return a rented bike. The admin has full control and visibility over the system through a dedicated dashboard and website, allowing them to monitor all student activities, manage bike rentals, track the location of each student via GPS on a real-time map, control rental timing for stations, and deactivate or activate the stations. The Firebase database serves as the centralised system for storing and managing all data. The smart bike is equipped with an RFID system and communicates with the connected vest using ESP modules configured as an access point and client. The system also includes directional detection to activate LED lights, enhancing safety by indicating when the bike stops or changes direction. Additionally, a locking mechanism provides security by locking the bike at the station when the user doesn’t return it on time or when the user goes outside of the college boundaries. BikeCampusHub offers a practical solution for student transportation within the university, combining convenience, security, and smart technology to improve campus mobility.